Evaluation of a Blend of Phytochemicals and Carboxylic Acid When Complete Feed and Soybean Meal Were Inoculated with Porcine Epidemic Diarrhea Virus, Porcine Reproductive and Respiratory Syndrome Virus, and Seneca Valley Virus 1 - Olivia L. Harrison; Jianfa Bai; Martee Larson; Roman M. Pogranichniy; Francisco Domingues; Nicole Holcombe; Othmar Lopez; Cassandra K. Jones (Kansas Agricultural Experiment Station Research Reports, 2024)
Chemical mitigants have been found to decrease virus concentrations in feed and ingredient matrices. Continued research is needed to identify the appropriate inclusion levels and application time for different viruses in these matrices. Therefore, the objective was to evaluate different inclusion levels of a product utilizing a synergistic blend of phytochemicals and carboxylic acid (PCA) when applied either pre- or post-inoculation of porcine epidemic diarrhea virus (PEDV), porcine reproductive and respiratory syndrome virus (PRRSV) and Seneca Valley virus 1 (SVV1) to complete feed or soybean meal. The experiment was designed in a 2 × 2 factorial with a PCA-based product, (Finio, Anitox Corp. Lawrenceville, GA) applied either before virus inoculation (pre-inoculation) or after inoculation (post-inoculation) at either 3.5 or 5.5 lb/ton. On d 0, samples of the respective matrices were weighed in 50 g aliquots and added to 500 mL bottles. The PCA blend was applied to the pre-inoculation samples at their respective inclusion levels and 50 μL each of 1×107 TCID50/mL PEDV, 1×108 TCID50/mL PRRSV, and 1×108 TCID50/mL SVV1 were added to the post-inoculation samples. All bottles were shaken and allowed to sit at room temperature for 24 hours. On d 1, virus was added to the pre-inoculation samples and chemical mitigants were added to the post-inoculation bottles. Half of the samples were immediately processed (0 hr) and the other half were incubated at room temperature for an additional 24 hours (24 hr). Samples were processed and aliquots were analyzed via a triplex PCR assay at Kansas State University Veterinary Diagnostic Laboratory. Cycle threshold and proportion of PCR positive were analyzed using SAS GLIMMIX v 9.4 (SAS, Inc., Cary, NC), with each virus and matrix combination analyzed individually. In both soybean meal and complete feed an application time × inclusion level interaction was only observed for PRRSV at 0 hr, where less PRRSV RNA was detected (P < 0.05) in the post-inoculation samples at either 3.5 or 5.5 lb/ton as compared to the pre-inoculation or control samples. For other viruses at 0 hr in complete feed and soybean meal, the post-inoculation samples had less detectable PEDV or SVV1 RNA (P < 0.05) than the pre-inoculation samples. As time continued (24 hr), both pre- and post-inoculation samples had less detectable PEDV RNA (P < 0.05) than the controls in complete feed. Interestingly, the positive controls had less detectable viral RNA (P < 0.05) at 24 hr in soybean meal compared to either the pre- or post-inoculation samples. This effect is hypothesized to reverse as the mitigated samples have a greater contact time. Overall, the use of a PCA-based product reduced viral concentrations in complete feed and had a variable effect when applied to soybean meal. More research is needed to understand the contact time required for viral reduction and the infectivity of these samples at defined contact times.
Keywords: complete feed; soybean meal; synergistic blend of phytochemicals and carboxylic acids; virus